Two complementary methods to control gonadotropin‐releasing hormone vaccination (Improvac®) misuse in horseracing: Enzyme‐linked immunosorbent assay test in plasma and steroidomics in urine. Issue 9 (2nd June 2017) - Bailly‐Chouriberry, Ludovic; Loup, Benoit; Popot, Marie‐Agnès; Dreau, Marie‐Laure; Garcia, Patrice; Bruyas, Jean‐François; Bonnaire, Yves
Abstract : Since the availability on the European market of the vaccine Improvac® dedicated to male pig immunological castration, the risk of misuse of this product in horses is now considered as a threat for the horseracing industry. Immunological castration is not allowed by the racing codes (immune system, Article 6). Indeed, this vaccination against the hypothalamic hormone luteinizing hormone‐releasing hormone or gonadotropin‐releasing hormone (GnRH) will prevent the release from the anterior pituitary of luteinizing hormone and follicle stimulating hormone, which are required for the development and activity of gonads in males (testes) and female (ovaries) and therefore all their subsequent physiological functions. This treatment will induce a strong hormonal variation resulting in a behaviour modification of the animals. In this work, four male standardbreds treated with Improvac® vaccine (two intramuscular injections within 4 weeks) were studied. Monitoring of the total scrotal width showed a decrease of the scrotum size (37%) and production of anti‐GnRH antibodies was detected up to 200 days after the first injection. Anti‐GnRH antibodies were detected in plasma after caprylic acid precipitation followed by an enzyme‐linked immunosorbent assay (ELISA) as a rapid and efficient screening method applicable to routine analysis. These results were correlated to a switch of the sexual status from male group to gelding/female group obtained by a steroidomic approach with urine based on ten endogenous compounds. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Two new analytical approaches are proposed to the horseracing industry to prevent Improvac ® misuse. These are an enzyme‐linked immunosorbent assay test to detect anti‐gonadotropin‐releasing hormone antibodies in plasma and a complementary study with urine by steroidomics. The two methods allow the control of immunological castration.